Green Diesel Engines Biodiesel Usage in Diesel Engines - Kegl, Breda. (Lecture Notes in Energy,, 2013)
With a focus on  ecology, economy and engine performance, diesel engines are explored in relation to current research and developments. The prevalent trends in this development are outlined with particular focus on  the most frequently used alternative fuels in diesel engines; the properties of various type of biodiesel and the concurrent improvement of diesel engine characteristics using numeric optimization alongside current investigation and research work in the field. Following of a short overview of engine control, aftertreatment and alternative fuels, Green Diesel Engine explores the effects of biodiesel usage on injection, fuel spray, combustion, and tribology characteristics, and engine performance. Additionally, optimization procedures of diesel engine characteristics are discussed using practical examples and each topic is corroborated and supported by current research and detailed illustrations. This thorough discussion provides a solid foundation in the current research but also a starting point for fresh ideas for engineers involved in developing/adjusting diesel engines for usage of alternative fuels, researchers in renewable energy, as well as to engineers, advanced undergraduates, and postgraduates.